Survival of Wild Strains of Lactobacilli During Kombucha Fermentation and Their Contribution to Functional Characteristics of Beverage - Dragoljub Cvetković; Aleksandra Ranitović; Dragiša Savić; Nataša Joković; Ana Vidaković; Lato Pezo; Siniša Markov (Polish Journal of Food and Nutrition Sciences, 2019)
Kombucha is a fermented tea beverage, which is traditionally prepared by fermenting sweetened black tea with tea fungus, which is a consortium of yeasts and acetic acid bacteria. In this paper, viability of selected wild strains of lactobacilli during Kombucha fermentation, their interaction with tea fungus and their contribution in obtaining a beverage of increased functional characteristics were tested. Five wild strains which were isolated from traditionally fermented foods were separately added on the second day of Kombucha fermentation. Count of yeasts, acetic acid bacteria and lactobacilli, as well as pH, titratable acidity, and content of L- and D-lactic acid during Kombucha fermentation were determined. Wild strains of lactobacilli demonstrated a differentiated survivability and the counts in fermentation broth ( i.e. Kombucha beverages) depending on the strain applied. The addition of wild Lactobacillus spp. during Kombucha fermentation had no effect on the physiological activity of tea fungus, but they contributed to a significant increase in lactic acid content in the beverage. The highest lactic acid content during Kombucha fermentation was produced by the strain of Lactobacillus plantarum isolated from 40-day-old cream, while the strain of Lactobacillus hilgardii (from sour dough) showed the highest viability.